A relief with Mithraic scenes on a sarcophagus lid: iconographic and literary issues. (November 2022) - Catenacci, Carmine; Domenicucci, Patrizio; Menozzi, Oliva
Abstract: During the excavations of the team of the University of Chieti in the area of Ain Hofra, in the East necropolis of Cyrene, several interesting sculptures were found in tombs A and C, also called the Tomb of the Sarcophagi and the Tomb of the Sculptures. In this paper a specific find from Tomb A is presented, as it is a rare example of a Mithraic relief from a private funerary context. The find has only previously been published for the translation and presentation of the inscription; however, an analysis and interpretation of the relief together with the inscription has never been tackled. The very fragmentary lid is made of white marble, presenting a very lively iconographic sequence of Mithraic schemata, in combination with a metrical inscription within a central tabula ansata . The find context is particularly monumental and is characterized by two Temple Tombs built in ashlar masonry located on the plateau of Ain Hofra overlooking the wadi (canyon) and the fertile terraces below. This multidisciplinary article looks at the iconographic elements, the epigraphic implications and the monumental context of the Mithraic reliefs.